Implementasi Eco-Socioentrepreneurship Pengolahan Pisang Retort Melalui Pemberdayaan Perempuan Kreatif Desa Kebonbimo Untuk Ketahanan Pangan - Donna Setiawati; Sigit Muryanto; Yunita Niqrisah Dwi Pratiwi; Erni Widarti; Aldino Afisandi Adnan Efendi; Niken Harjutri; Calista Ika Febriana; Kustiyana Nuraini (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Kebonbimo Village, Boyolali Regency, has economic potential through the agricultural and tourism sectors, particularly with the Umbul Tlatar tourist attraction. However, this tourist attraction currently lacks a specialty food souvenir that could enhance regional identity and enhance local economic value. This Community Service activity aims to empower women's groups in Kebonbimo Village through banana processing using retort and vacuum frying techniques. This program implements eco-socioentrepreneurship to increase the added value of local commodities and strengthen food security. The project partners are KWT Azalea Farm and KUB Putri Bima. Implementation methods include program preparation, program outreach, program implementation, monitoring and evaluation, mentoring, and program sustainability. The results of the activity demonstrate an increase in the women's group's ability to produce ready-to-eat banana snacks that are safe, hygienic, have a crispy texture, an attractive flavor, and a longer shelf life.